PENGARUH PEMBERIAN BOKASHI KAYAMBANG TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) PADA TANAH GAMBUT (The Effect of Giving Bokashi Kayambang on Growth of oil Palm (Elaeis guineensis Jacq) on Peat) - yani,, Suri; Y., Sulistiyanto,; S, Zubaidah,; tiyah, Sus (AGRIPEAT, 2015)
ABSTRAKThis study aims to determine the effect of giving kayambang bokashi (Salvinia molesta) on the growthof oil palm seedlings on peat. The research was conducted at land of Analytical laboratoryPalangkaraya University, from July to October 2011. This research used Completely RandomizedDesign (CRD) single factor consisting of four treatments are: 0 ; 0,5; 1,0; and 2,0 kg. Bokashikayambang polibag-1). Each treatment was repeated 6 times to obtain 24 units of the experiment. Theresults showed that bokashi kayambang has effect on height increment, increment the number of stemleaves and wet and dry weight of oil palm seedlings. There is no significantly different on stemdiameter increment, leaf area, root length and number of roots. Bokashi kayambang a dose of 2 kg.Polybag-1 provides a real impact and can improve the wet and dry weight of oil palm seedlings.Key word : Oil Palm, Bokashi Kayambang, Peat